1986
DOI: 10.1192/bjp.148.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder, Drinking and Alcoholism:

Abstract: We studied 371 psychiatric admissions in an attempt to relate primary and secondary diagnosis, psychopathology, and stated reasons for drinking to alcohol consumption and alcoholism. No diagnostic group other than the alcoholics drank significantly more than the mean, and the schizophrenics drank less. One-third of those with bipolar and minor depression increased their drinking in the month before admission, but this was almost offset by those with similar diagnoses who drank less. Alcoholism, though not alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…It was found that alcoholism is significantly less common in the relatives of schizophrenics than in the relatives of controls. This corroborates Bernadt & Murray's (1986) finding that patients diagnosed as schizophrenics drank less in the month before admission to hospital than other patients admitted to a psychiatric hospital. In a further study, Kendler (1985) investigated the monozygotic and dizygotic co-twins of index twins diagnosed as having both schizophrenia and alcoholism.…”
Section: Alcoholism and Schizophreniasupporting
confidence: 80%
See 1 more Smart Citation
“…It was found that alcoholism is significantly less common in the relatives of schizophrenics than in the relatives of controls. This corroborates Bernadt & Murray's (1986) finding that patients diagnosed as schizophrenics drank less in the month before admission to hospital than other patients admitted to a psychiatric hospital. In a further study, Kendler (1985) investigated the monozygotic and dizygotic co-twins of index twins diagnosed as having both schizophrenia and alcoholism.…”
Section: Alcoholism and Schizophreniasupporting
confidence: 80%
“…Freed (1975) Rimmer & Jacobsen (1977) Hbrec & Ommen (1982) Schuckit (1982) Cook & Winokur (1985) Kendler era/. (1985) Kendler (1985) Bernadt & Murray (1986) No association between a history of psychotic symptoms and a personal, or family history of schizophrenia Alcoholic relatives of alcoholic probands with psychotic symptoms were significantly more likely to have psychotic symptoms than relatives related to alcoholic probands without psychotic symptoms Alcoholism less common in relatives than in controls Both disorders alone and in combination are more common in 'MZ' than in 'DZ' co-twins Alcoholic psychosis significantly more common in 'MZ' than 'DZ' index twin; no significant difference in frequency of total schizophrenia, total alcoholism, schizophrenia only and alcoholism only, in the co-twins of index twins, with versus without a diagnosis of alcoholic psychosis Schizophrenics drank less than the mean amount drunk by patients admitted to hospital.…”
Section: Alcoholism and Schizophreniamentioning
confidence: 99%
“…In several studies the prevalence of alcohol abuse among schizophrenics is as high as the abuse in other psy chiatric samples or even lower [34]. Higher consumption is shown in studies by Altcrman [24], Drake et al [30] and Dixon et al [23].…”
Section: Harmful Use Of Psychotropic Substances By Schizophrenicsmentioning
confidence: 83%
“…Foremost, they are commonly co-morbid (Merikangas et al, 2008) with the bipolar spectrum being associated with cocaine (Cocores et al, 1987;Maremmani et al, 2008;Nunes et al, 1989;Perugi et al, 2012;Post and Kalivas, 2013;Weiss and Mirin, 1986), cannabis (Arias et al, 2013;Ashton et al, 2005;Do and Mezuk, 2013;Maremmani et al, 2000bMaremmani et al, , 2004Maremmani et al, , 2006a, benzodiazepines (Brunette et al, 2003;Lin et al, 2011;Perugi et al, 2002), alcohol (Bernardt and Murray, 1986;Brousse et al, 2008;Chengappa et al, 2000;Farren et al, 2013;Fletcher et al, 2013;Freed, 1969;Nery et al, 2010;Weiss and Mirin, 1989) and heroin (Maremmani, 2013;Maremmani et al, 2014a). Indeed, because bipolar spectrum disorders and addiction are so often comorbid, each operates as reciprocal risk factors and should be viewed from a unified perspective (Camacho and Akiskal, 2005;Maremmani et al, 2006b).…”
Section: Bipolar Disorder In Homeless Populationsmentioning
confidence: 96%